Determination Of Elective Course Based On Hierarchical Fuzzy Topsis Method With Matlab Software. - DOĞANALP, Burcu; DOĞANALP, Serkan (Selcuk University Social Sciences Institute / Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2016)
The determination of elective course in undergraduate education is an important decision making process, because the course chosen allows the students to specialize in the area they are interested in. The aim of this study is to apply Hierarchical Fuzzy TOPSIS (HFTOPSIS) method in determining elective course as a fuzzy multi-criteria decision making (FMCDM) technique and introduce the programme developed in MATLAB software related to this decision making process. In this study, a decision model based on the process of determining elective course belonging to the sixth semester of third year students receiving education in economics department at a state university is developed. The assessments of the importance weights of the main and sub-criteria used in determining elective course and the assessments of the elective courses opened in the sixth semester in terms of the sub-criteria are performed by using linguistic variables. Then, these linguistic data are transformed into triangular fuzzy numbers, used in two different algorithms of HFTOPSIS and, relevant process is programmed, and the results of the two algorithms are compared. In the study it is concluded that the most important decision criteria for determining the elective course is elements relating to the lecturer (0.76, 0.96, 1.00). According to the two algorithms, the candidate elective courses are ranked from the best to the worst with respect to the calculated closeness coefficients. The ranking order of three alternative elective courses is similar according to the two approaches handled in the study, and it is as A>A> A. It is seen that the most appropriate elective course is A with a closeness coefficient 0.821 according to the first approach and 0.819 according to the second approach. When the evaluation about whether the choice is risky or not via the closeness coefficient of elective course A is made, it can be expressed that the alternative chosen is "approved and preferred".